Multi-body wave function of ground and low-lying excited states using unornamented deep neural networks - Tomoya Naito (内藤智也); Hisashi Naito (内藤久資); Koji Hashimoto (橋本幸士) (Physical Review Research, 2023)
We propose a method to calculate wave functions and energies not only of the ground state but also of low-lying excited states using a deep neural network and the unsupervised machine learning technique. For systems composed of identical particles, a simple method to perform symmetrization for bosonic systems and antisymmetrization for fermionic systems is also proposed.